Implementasi Automated Conflict Testing Untuk Mencegah Double Booking Pada Sistem Penjadwalan Klinik Gigi - Sulthan Zahran Sunata; Wahyu Catur Wibowo (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Double booking poses a significant risk to dental clinic scheduling systems, as it disrupts service workflows, increases patient wait times, and reduces practitioner operational efficiency. While healthcare scheduling literature extensively covers slot optimization, resource allocation, and no-show issues, there is limited research demonstrating how conflict prevention rules are automatically validated within implemented clinic systems. Conversely, software testing literature tends to focus on general automation rather than executable testing for rule-based conflict checking. This study aims to implement automated conflict testing to verify double-booking prevention mechanisms in a Django REST API-based dental clinic scheduling system. The methodology involves automated testing at both the model and API levels, utilizing scenarios derived from conflict-checking business rules. Test results indicate that all scenarios passed and that conflict-checking rules were consistently applied to both initial booking and rescheduling processes. The study's primary contribution is an executable, structured automated conflict-testing approach that confirms the acceptance of back-to-back slots, the rejection of active overlaps, and the subjection of rescheduling requests to conflict validation.